Analyzing health inequality among adolescents in Chile: Physical activity socioeconomics, and play environments across genders - De Moraes-Ferrari, G (ELSEVIER, 2025)
Objectives: This study examines the association between socioeconomic factors, gender, physical activity, and health satisfaction among Chilean adolescents. It aims to identify key disparities and their implications for public health policies. Study design: Cross-sectional study based on the third wave (2016-2019) of the international Children s Worlds survey. Methods: A total of 911 adolescents aged 12-13 years from Santiago, Chile, participated. Physical activity levels, socioeconomic indicators, and health satisfaction were assessed. Statistical analyses included t-tests, chi-square tests, ANOVA, and multiple linear regression models stratified by gender. Results: Boys reported higher levels of electronic gaming (64.6 % vs. 35.4 %, p < 0.001), while girls engaged more in outdoor play at lower frequencies (52.8 % vs. 47.2 %, p = 0.045). Perceived safety was a stronger predictor of health satisfaction for girls ((3 = 0.252, p < 0.001) than for boys ((3 = 0.251, p < 0.001). Conclusions: Socioeconomic and environmental factors significantly influence adolescent health satisfaction, with gender-specific differences. Policies should focus on improving access to recreational spaces and addressing economic barriers, particularly for girls.